Post-Pandemi Covid-19 Government Relaxation Policies And Its Implications For Sharia Bank Performance - Hasnil Hasyim; Sujian Suretno (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2023)
Banking as an intermediary institution based on the Sharia Banking Act No. 21 of 2008 mandates collect and distribute funds to the public in a proportionate manner. Proportion means is that the portion that is collected and that which is distributed should be balanced, so that the expected profit maximum. In the 2020 era there was the emergence of the Covid 19 pandemic which resulted in the collection and disproportionate distribution of funds. Funding cannot be channeled optimally, because it is work more focused on improving existing financing as a result of customer defaults due to repayment capacity changes. Conditions that cannot be predicted in advance. Government with authority issued a relaxation policy in the form of restructuring through the Financial Services Authority (OJK) provide solutions that are solutive for customers and banks. Over time customer financing saved and doing well. However, nearing the end of the policy there were many related internal audit findings the quality of the policy. Many customers are policy-justified in current collectibility, but in fact collectibility Non Performance Finance (NPF), namely in the collectibility category 3.4 and 5. Under these conditions, it is certain that the bank will incur a loss due to the provision of Reserves Impairment Losses ( CKPN) formed. Cleansing data carried out on several customers shows that customers already have qualities that cannot be saved as a result of implementing policies government that does not have a time limit, so that within that unspecified period of time have a fatal impact on the quality of customers and have an impact on banking performance or the soundness level of the bank worsened.